Trends of print books usage among academic communities - ARSHAD, Alia; Ameen, Kanwal; Jabeen, Safia (Qualitative and Quantitative Methods in Libraries, 2021)
Abstract The purpose of the study is to examine usage patterns of print books in terms of checked out by subject, publication date, faculty, user categories and months using ‘Transaction Log Method’. Checked out books log data for one year was collected through library information system (MLIMS) taking University of the Punjab’s central library as a sample. Findings depict that undergraduate and graduate students checked out most of the books, while academic and administrative staff checked out least number of books. Library users from the faculty of Education, Science and Law checked out most of the books. Results also showed that Literature, Social Science and Religion books were mostly checked out as compared to Natural Science and Technology books. The study is unique in Pakistani scenario as no previous study investigated use patterns of print books in a university setting using log data of the checked out books. The findings are consistent with other studies from the developed countries.